2000
DOI: 10.1176/appi.ajp.157.11.1782
|View full text |Cite
|
Sign up to set email alerts
|

Feeling Unreal: A PET Study of Depersonalization Disorder

Abstract: Depersonalization appears to be associated with functional abnormalities along sequential hierarchical areas, secondary and cross-modal, of the sensory cortex (visual, auditory, and somatosensory), as well as areas responsible for an integrated body schema. These findings are in good agreement with the phenomenological conceptualization of depersonalization as a dissociation of perceptions as well as with the subjective symptoms of depersonalization disorder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
114
3
5

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 263 publications
(132 citation statements)
references
References 33 publications
10
114
3
5
Order By: Relevance
“…31,32 Röeder and colleagues 33 found reduced amygdala activity during induced depersonalization in healthy control participants. Taken together, these findings suggest that reduced temporal activity is a potential correlate of dissociation and reduced pain sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…31,32 Röeder and colleagues 33 found reduced amygdala activity during induced depersonalization in healthy control participants. Taken together, these findings suggest that reduced temporal activity is a potential correlate of dissociation and reduced pain sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…Yen Pik Sang et al [120] reported that caloric vestibular stimulations in healthy subjects may induce transient symptoms of depersonalization and derealisation (''body feels strange/different in some ways'', ''feeling of detachment or separation from surroundings'') by a disintegration in personal space and/or disintegration between personal and extrapersonal space. In a PET study on depersonalization, Simeon et al [106] found brain activation changes related to embodiment in regions that have also been shown to be activated by caloric vestibular stimulation, such as the superior temporal gyrus, posterior insula and inferior parietal lobule [19,20,39,47,50,112]. Collectively, these findings suggest that caloric vestibular stimulation interferes with self-processing and embodiment, also inducing symptoms of depersonalization, which share several aspects with out-ofbody experiences [105].…”
Section: Effects Of Natural and Artificial Vestibular Stimulations Onmentioning
confidence: 99%
“…DPD is characterised by a persistent or recurrent disruption in self-awareness typically revolving around feelings of disembodiment and a subjective emotional numbing (see Table 1: Sierra, 2009;Sierra & David, 2011;Simeon et al, 2000). Patients often describe feeling detached or estranged from themselves, from their bodies and from their emotions.…”
Section: Introductionmentioning
confidence: 99%